Large cell neuroendocrine carcinoma: retrospective analysis of 24 cases from four oncology centers in Turkey. Issue 2 (22nd April 2013) - Ustaalioglu, Bala Başak Oven; Ulas, Arife; Esbah, Onur; Turan, Nedim; Bilici, Ahmet; Demirci, Umut; Alkıs, Necati; Seker, Mesut; Oksuzoglu, Berna; Gumus, Mahmut
Abstract Background: Large cell neuroendocrine carcinoma (LCNEC) of the lung is classified as a variant of large cell lung carcinoma by the World Health Organization, however, the clinical and biological behavior of LCNEC resembles small cell lung carcinoma (SCLC) with a high mitotic index and a positivity of tumor cells with neuroendocrine markers. As there have only been a small number of patients with LCNEC recorded in literature, there is no consensus about the management of this subset. In the present study, we evaluated the incidence and prognosis of LCNEC in four oncology centers in Turkey. Method: We analyzed 24 patients with diagnoses of LCNEC from 3138 non‐small cell lung cancer patients who were diagnosed and treated between 2008 and 2010 in four different medical oncology centers in Turkey. Results: The median age was 56 (range; 36–64) and most patients were male, with three women included in the study. Ten out of 24 patients (41.6%) had locally advanced or metastatic disease, therefore, surgery could not be performed. Five patients (20.8%) were staged with stage I, six (25%) with stage II, five (20.8%) with stage III, and eight (33.3%) with stage IV. All patients had a history of smoking. Nine patients received chemotherapy postoperatively. At the 14.4‐month follow‐up period (range; 3–59) the median overall survival (OS) and progression‐free survival (PFS) rates were 32.7 and 9.5 months respectively. Tumor, node, metastasis (TNM) stage, performance status (PS) and the performance of surgery were significantly related to rates of both OS and PFS (P < 0.05). Conclusion: LCNEC was generally diagnosed postoperatively. Prognosis of LCNEC is poor and surgery has not proven an effective solution for long‐term survival, therefore, adjuvant chemotherapy has been suggested.